Analisis Kesulitan Siswa Pada Materi Geometri Melalui Model Problem Based Learning (PBL) - Afa Zahra; Annisa Azzahra; Putri Nur Anggraeni (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
Understanding and determining fold symmetry is a competency that is difficult for students to achieve, either because the learning does not attract student enthusiasm or the students themselves do not have the motivation to learn about fold symmetry. In connection with this, this research was conducted with the aim of knowing student learning outcomes on folded symmetry material using the Problem Based Learning (PBL) model. This research is a type of research that uses quantitative descriptive methods with an approach in the form of a classroom action approach. The source of this research comes from SD Negri 079 Pajagalan and the subjects in this research are class III students at SD Negri 079 Pajagalan. The technique for collecting data on student learning outcomes is carried out through tests in the form of test questions from evaluations and student worksheets. Then the data obtained was analyzed descriptively. Research that has been conducted shows that the difficulties experienced by students actually come from the questions given not being in accordance with the students' cognitive abilities.